2015
DOI: 10.1007/s10286-015-0270-5
|View full text |Cite
|
Sign up to set email alerts
|

Non-dipping nocturnal blood pressure and psychosis parameters in Parkinson disease

Abstract: Financial disclosure:The authors declare that the research was conducted in the absence of any commercial or financial relationships that could be construed as a potential conflict of interest.Funding sources for study: None 2Background: Non-motor symptoms are increasingly recognized in Parkinson's Disease (PD) and include physical as well as psychological symptoms. A psychological condition that has been well studied in PD is psychosis.Cardiovascular autonomic dysfunction in PD can include a reversed or lack … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 49 publications
0
2
1
Order By: Relevance
“…BP disturbances are associated with cardiovascular and renal conditions, including high risk of terminal-organ injury, particularly to the heart (left ventricular hypertrophy, CHF, and myocardial infarct), brain (stroke), and kidney (albuminuria and progression to end-stage renal failure) [ 18 ]. The majority of previous studies which analyzed BPI in the aforementioned pathologies showed participants to have non-dipper BPI values [ 41 , 42 ]; however, our results showed the BPI values of the group (presenting with different chronic conditions) to be even inverse-dippers (see Figure 1 ). These even higher blood pressure values at night, significantly more present in women than in men, did not show any hypoalgesia effect in both men and women, which means that our patient group suffering from chronic pain does not react with any pain killing mechanism caused by higher blood pressure in other populations.…”
Section: Discussioncontrasting
confidence: 65%
“…BP disturbances are associated with cardiovascular and renal conditions, including high risk of terminal-organ injury, particularly to the heart (left ventricular hypertrophy, CHF, and myocardial infarct), brain (stroke), and kidney (albuminuria and progression to end-stage renal failure) [ 18 ]. The majority of previous studies which analyzed BPI in the aforementioned pathologies showed participants to have non-dipper BPI values [ 41 , 42 ]; however, our results showed the BPI values of the group (presenting with different chronic conditions) to be even inverse-dippers (see Figure 1 ). These even higher blood pressure values at night, significantly more present in women than in men, did not show any hypoalgesia effect in both men and women, which means that our patient group suffering from chronic pain does not react with any pain killing mechanism caused by higher blood pressure in other populations.…”
Section: Discussioncontrasting
confidence: 65%
“…The pathological nocturnal profiles are reverse dipping, reduced dipping, and extreme dipping, described in 477 (40.46% of the patients evaluated for this), 310 (35.67%) and 23 (5.1%) subjects, respectively. In one study, PD patients with reduced dipping were more prone to psychotic symptoms [35], but not to depression [34]. Those with reverse dipping had more severe non-motor manifestations such as cognitive decline [16][17][18]24], anxiety [16,17] and autonomic symptoms [16,17,23,39].…”
Section: Resultsmentioning
confidence: 98%
“…The abnormalities in the circadian rhythm of BP in PD have been described decades ago ( Senard et al, 1992 ) and, more recently, Tanaka et al (2018) found that the nocturnal riser profile was cross-sectionally associated with the presence of dementia (odds ratio 11.6), while the physiological dipper pattern (a reduction in nighttime BP greater than 10% with respect to daytime BP) was almost inexistent in the demented group (<4%). Similarly, non-dipper PD patients also show higher degree of psychotic symptoms ( Stuebner et al, 2015 ). Non-dipping and riser profiles seem independent of age, gender, disease duration, age at onset, the severity of the disease, the use of anti-PD drugs and vitamin D level ( Arici Duz and Helvaci Yilmaz, 2020 ).…”
Section: Nocturnal Blood Pressure Profile and Cognitive Declinementioning
confidence: 99%